Hubungan Antara Pengetahuan Dan Sikap Dengan Kepatuhan Diit Diabetes Mellitus (DM) Pada Lanjut Usia (Lansia) Di Kelurahan Gayam Kecamatan Sukoharjo - NOVITASARI, RETNANINGTYAS; , Agus Sudaryanto, S.Kep., Ns., M.Kes; , Dian Nur W, S.Kep., Ns (RETNANINGTYAS NOVITASARI, 2015)
The adherence's diabetes mellitus patients to the diet of eldery with diabetes mellitus was generally still low. There were about 75% of elderly with diabetes mellitus were not obeying. The rule of the diet Sukoharjo district was one of the district with high diabetes mellitus cases, there were about 1.138 case, one of cases was taken place in Gayam Village which had 77 cases of diabetes mellitus. Based interview found that 70% of respondens did not obeying to diet diabetes mellitus. The knowledge and attitude of the diabetes mellitus's suffers have an important role to prevent and suppress the occurrence of complication. The aim of this study was to know the relationship between the knowledge and attitude with diabetes mellitusdiet adherence of the elderly in Gayam village sub district of Sukoharjo. This research adopted descriptive correlational method with cross sectional approach. The sample was taken by using total sampling technique with 77 respondents. The Chi Square (X2) and Fisher's test were used to analyze the data. The result of this research showed that most respondents have enough knowledge and attitude, and adherence toward diabetes mellitus.The conclusion of this research, there is a significant correlation between the knowledge and diabetes mellitusdiet adherence of the elderly in the Gayam village sub district Sukoharjo proven by value (p = 0.031), and a significant correlation between the attitude and diabetes mellitusdiet adherence of the elderly in the Gayam village sub district Sukoharjo, evidenced by value (p = 0.040).